Exclusionary and Exploitative Racism: Empirical Analyses of Two Facets of Contemporary Racial Ideologies - Martin Wolgast; Sima Nurali Wolgast (Nordic Journal of Migration Research, 2024)
Objectives: The article discusses and tests a series of hypotheses regarding the distinction between exclusionary and exploitative aspects of contemporary racial ideologies. Central to exclusionary racism are negative attitudes regarding ‘non-white’ immigration and the belief that the racialised other is competing for resources and social benefits. In contrast, the core of exploitative racism is that the racialised ‘other’ can be used to increase profit and render certain services cheaper and more available. Method: Data from a large-scale survey on the Swedish labour market was used to test the validity of a model representing exclusionary and exploitative racism as separate facets of racial ideologies and to test hypotheses regarding how these two facets relate to socioeconomic status and an established measure of racial ideology (modern racism). Results: The results indicate that the distinction between exclusionary and exploitative racism can be empirically motivated. Additionally, socioeconomic status was found to be negatively associated with exclusionary racism, but positively associated with exploitative racism, and exclusionary racism was found to be strongly associated with modern racism. The results are discussed in relation to previous research regarding the racialised nature of western societies and the role of racial ideologies in reproducing racial hierarchies.